The cardioprotective effect of whey protein against thioacetamide-induced toxicity through its antioxidant, anti-inflammatory, and anti-apoptotic effects in male albino rats - Almohawes, Zakiah Nasser; Okail, Hanan A.; Al-Megrin, Wafa A.; El-Khadragy, Manal F.; Ibrahim, Mona A.; Fathalla, Ayah S.; Soliman, Doaa; Mohamed, Sherif R. (Frontiers in Veterinary Science, 2025)
IntroductionThioacetamide (TAA) is widely used as an experimental drug in liver disease studies and has been shown to exert toxicity across multiple organs. It has been linked to oxidative stress, inflammation, apoptosis, fibrosis, and epigenetic modifications. Whey protein (WP) provides an abundant supply of essential and non-essential amino acids that are vital for the human body. It is highly valued for its nutritional and biological properties, benefiting the immune, digestive, cardiovascular, neurological, and endocrine systems. This research sought to evaluate the possible protective effects of WP against TAA-induced cardiotoxicity in rats, emphasizing its antioxidant, anti-inflammatory, and anti-apoptotic mechanisms.MethodsA total of forty male rats were randomly divided into four groups, with each group containing ten rats: the control group, the TAA-treated group (100 mg/kg body weight), the WP-treated group (300 mg/kg body weight), and the WP + TAA group. The treatments were administered for three consecutive weeks.ResultsThe findings revealed that TAA exposure significantly reduced cardiac tissue activities of glutathione, superoxide dismutase, and catalase while markedly increasing malondialdehyde and nitric oxide activities. Additionally, TAA administration led to a significant elevation in inflammatory markers (TNF-α and IL-1β) and apoptotic markers (Bax and Bcl-2), along with increased caspase-3 gene expression in heart tissue. Serum levels of lactate dehydrogenase were also notably higher in the TAA-intoxicated group, accompanied by significant histopathological alterations, increased collagen fiber deposition, and a pronounced immunopositive reaction for TGF-β1 and NF-κB in heart tissue. However, pre-treatment with WP significantly alleviated TAA-induced cardiotoxicity by reducing oxidative stress, inflammatory response, and apoptotic markers in cardiac tissue.DiscussionThe results indicate that WP supplementation offers protective effects and mitigates the cardiotoxicity triggered by TAA.